Macrotextured Breast Implants with Defined Steps to Minimize Bacterial Contamination around the Device: Experience in 42, 000 Implants. Issue 3 (September 2017) - Adams, William P.; Culbertson, Eric J.; Deva, Anand K.; R. Magnusson, Mark; Layt, Craig; Jewell, Mark L.; Mallucci, Patrick; Hedén, Per
Abstract : Background: Bacteria/biofilm on breast implant surfaces has been implicated in capsular contracture and breast implant–associated anaplastic large-cell lymphoma (ALCL). Macrotextured breast implants have been shown to harbor more bacteria than smooth or microtextured implants. Recent reports also suggest that macrotextured implants are associated with a significantly higher incidence of breast implant–associated ALCL. Using techniques to reduce the number of bacteria around implants, specifically, the 14-point plan, has successfully minimized the occurrence of capsular contracture. The authors hypothesize that a similar effect may be seen in reducing the risk of breast implant–associated ALCL. Methods: Pooled data from eight plastic surgeons assessed the use of macrotextured breast implants (Biocell and polyurethane) and known cases of breast implant–associated ALCL. Surgeon adherence to the 14-point plan was also analyzed. Results: A total of 42, 035 Biocell implants were placed in 21, 650 patients; mean follow-up was 11.7 years (range, 1 to 14 years). A total of 704 polyurethane implants were used, with a mean follow-up of 8.0 years (range, 1 to 20 years). The overall capsular contracture rate was 2.2 percent. There were no cases of implant–associated ALCL. All surgeons routinely performed all 13 perioperative components of the 14-point plan; two surgeons do not routinely prescribe prophylaxis for subsequent unrelated procedures. Conclusions: Mounting evidence implicates the role of a sustained T-cell response to implant bacteria/biofilm in the development of breast implant–associated ALCL. Using the principles of the 14-point plan to minimize bacterial load at the time of surgery, the development and subsequent sequelae of capsular contracture and breast implant–associated ALCL may be reduced, especially with higher-risk macrotextured implants. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.